Menschwerdung oder Buchwerdung des Wortes Gottes?: zur Logozentrik von Christentum und Islam - Gäde, Gerhard (Zeitschrift für katholische Theologie, 2010)
Traditionally Judaism, Christianity, and Islam are termed »book religions«. Christianity, however, is far less book-centered than Islam; the Bible is merely a pointer to the Christ-centeredness of Christianity. This opens up the question of a hermeneutic of the word of God, which in turns offers a few suggestions as to the conditions and prerequisites needed to appreciate the Quran as the Word of God in some sense.